Kegljanje na deset kegljev - "bowling" - Valenčak, Mihael (Šport (Ljubljana), 2016)
In English, the word "bowling" can be understood in a variety of ways: nine-pin bowling, ten-pin bowling, bocce ball and so on. For the purpose of this paper, the term will be confined to that of ten-pin bowling. The intention of this paper is to present the game of "bowling" to the Slovene public. The game, played by millions of people worldwide, will be introduced so as to appeal to both amateurs and experienced bowlers alike. In this paper, I have summarized the historical beginnings of the game both at home and abroad, detailing its modern development and focusing particularly on the United States of America (USA) as the founders of the modern game. I have also described the development of "bowling" in Slovenia. Additionally, I have also illustrated a portion of the equipment in detail: the ball, which is a vital component of the game and the shoes. Also included is a detailed description of the lane with all of its characteristics and features as well as the positioning of the pins, arrows and dots that help us to play the game. At the end, I have devoted a few words to parents on how to prepare a child to go to a bowling alley with all of its peculiarities, how to help them choose a suitable ball and enjoy the game. With the introduction of bowling to the Slovenian word, my goal was to contribute to the popularization of this sport in our country. I hope to soon meet one of my readers playing on the lane next to mine.
Keywords: bowling; equipment; kegljanje; kegljanje na deset kegljev; oprema; sport; šport; ten pin bowling